Firm Structural Attributes and Capital Structure Adjustments among Listed Manufacturing Firms in Nigeria using Static and Dynamic Approaches - Ibrahim, Jimoh; Olalere Adebayo, Aderemi; Kolawole Olowookere, Johnson; Zaid Adeyemi , Adewumi; Moromoke Oladejo , Titilayo (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The study examined the effect of firm structural attributes on capital structure adjustments of Nigerian listed manufacturing companies. Out of the 56 listed firms 35 listed manufacturing firms were selected using the purposive sampling approach. Dynamic and static estimation techniques were applied. The results from both static and dynamic panel data revealed that assets tangibility had a positive and significant effect on capital structure adjustments with (t= 4.463; t = 2.965; p <0.05). Non-debt tax shields (t= -2.831; t= -4.478; p <0.05) had negative but significant effect on capital structure adjustments. Furthermore, static result showed that firm size (t= -5.617; p <0.05) had negative but significant while dynamic results revealed firm size (t=6.956; P<0.05) had a positive and significant effect on capital structure adjustments. This study concluded that structural attributes serve as firm-level determinants to understanding of factors influencing the capital structure and speed of adjustments of listed companies in Nigeria. It was recommended that management of firms need to expand in size and investing in tangible assets to enhance their profit level, this will enable them to enjoy large profit levels with a large reduction in debt ratio.